Lived experiences of patients recovered from Covid-19: An interpretive phenomenological study - Shima Sadat Aghahosseini (Tehran University of Medical Sciences, 2021)
Background & Aim: Covid-19 is an emerging disease that has become a health crisis in the world and affected various aspects of human's life. Understanding the experience of patients with this disease is essential for proper and comprehensive care. The aim of this study was to explore the lived experiences of patients recovered from Covid-19. Methods & Materials: The present study was a qualitative study with an interpretive phenomenological approach that was conducted in 2021. For this purpose, 13 patients recovered from Covid-19 were selected using the purposive sampling method based on the inclusion criteria. In-depth, semi-structured interviews were used to collect the data. The interviews were recorded. Having transcribed the interviews, the transcripts were analyzed by a hermeneutic approach using the Van Manen method. Results: Data analysis revealed four main themes: "fear of imminent death", "living in a fence", "family worries", and "the limitations suffering". Conclusion: Patients' experiences of being infected with Covid-19 showed that the disease affected the physical, psychological, economic, social and family dimensions of individuals. Therefore, understanding the challenges, experiences and concerns of patients about the disease, can help executive decision-makers, healthcare providers and mental health professionals to comprehensively understand the consequences of the disease.